What's in a grade? Grading policies and practices in principles of economics. Issue 4 (1st October 2016) - Walstad, William B.; Miller, Laurie A.
ABSTRACT: Survey results from a national sample of economics instructors describe the grading policies and practices in principles of economics courses. The survey results provide insights about absolute and relative grading systems used by instructors, the course components and their weights that determine grades, and the type of assessment items used for the major course components of exams, quizzes, and homework. The survey also provides information about the discretionary grading practices of instructors related to awarding bonus points, giving extra credit, or setting cut points for grade decisions. The overall finding is that there is a wide variety of grading policies used in principles courses and substantial discretion in how economics professors determine grades.